Eco-toxicology and Control of Indian Desert Gerbille - Prakash, Ishwar (Indian Forester, 1964)
The paper embodies the observations on toxicity, relative acceptability and killing efficiency of four poisons and four proprietary rodenticides for the Indian desert gerbille, Meriones hurrianae. These are given as under:- 1. Racumin is the most toxic for the desert gerbilles. Dethmor and Ratafin, the two other anti-coagulants are also highly toxic but rodeth has low toxicity for these rodents. Among other poisons, Thallium sulphate and Zinc pbosphide are very toxic whereas Arsenious oxide and Barium carbonate have comparatively low toxicity. 2. Zinc phosphide, being quick acting, is recommended for field operations at 2% concentration with wheat flour. 3. Ratafin is most acceptable whereas racumin is consumed least when given to them, mixed with wheat flour. 4. There were no well marked symptom of Arsenic and barium poisoning. Heart becomes engorged due to Thallium sulphate poison. Coumarin derivatives caused bleeding from ear, nose, mouth and anus. Gerbils died due to paralysis when Ratafin was administered.